Baby-directed umbilical cord clamping: A feasibility study. (October 2018) - Blank, Douglas A.; Badurdeen, Shiraz; Omar F Kamlin, C.; Jacobs, Susan E.; Thio, Marta; Dawson, Jennifer A.; Kane, Stefan C.; Dennis, Alicia T.; Polglase, Graeme R.; Hooper, Stuart B.; Davis, Peter G.
Abstract: Introduction: Over five percent of infants born worldwide will need help breathing after birth. Delayed cord clamping (DCC) has become the standard of care for vigorous infants. DCC in non-vigorous infants is uncommon because of logistical difficulties in providing effective resuscitation during DCC. In Baby-Directed Umbilical Cord Clamping (Baby-DUCC), the umbilical cord remains patent until the infant's lungs are exchanging gases. We conducted a feasibility study of the Baby-DUCC technique. Methods: We obtained antenatal consent from pregnant women to enroll infants born at ≥32 weeks. Vigorous infants received ≥2 min of DCC. If the infant received respiratory support, the umbilical cord was clamped ≥60 s after the colorimetric carbon dioxide detector turned yellow. Maternal uterotonic medication was administered after umbilical cord clamping. A paediatrician and researcher entered the sterile field to provide respiratory support during a cesarean birth. Maternal and infant outcomes in the delivery room and prior to hospital discharge were analysed. Results: Forty-four infants were enrolled, 23 delivered via cesarean section (8 unplanned) and 15 delivered vaginally (6 via instrumentation). Twelve infants were non-vigorous. ECG was the preferred method for recording HR. Two infants had a HR < 100 BPM. All HR values were >100 BPM by 80 s after birth. Median time to umbilical cord clamping was 150 and 138 s in vigorous and non-vigorous infants, respectively. Median maternal blood loss was 300 ml. Conclusions: It is feasible to provide resuscitation to term and near-term infants during DCC, after both vaginal and cesarean births, clamping the umbilical cord only when the infant is physiologically ready.